German Children's Literature for Foreign Language Literacy and Character Education: A Case Study at SMA YARI Padang - Hawa, Andina Meutia; Pratiwi, Anne; Pratiwi, Dyani Prades; Nesa, Fakhria; Firmansyah, Okta; Saniro, Roma Kyo Kae; Arbain, Armini; Hamidi, Ahmad (Andalas International Journal of Socio-Humanities, 2025)
Foreign languages in Indonesia are often taught as supporting subjects, with English being the most common. German has also been introduced in some schools, including SMA YARI Padang. However, German lessons at this school have been discontinued over the last two years due to a lack of teaching staff. This study examined the use of German children's literature to enhance foreign language literacy and character development. A case study approach involved storytelling, interactive quizzes, observation, and mentoring. The storybook Ginting und Ganteng was chosen as a learning material because it was enjoyable and engaging for students to read and learn from. The results showed that children's literature helped students remember basic German vocabulary, learn new words in context, and better understand the story that was read. Furthermore, the story encouraged students to reflect on positive values such as honesty, kindness, and respect. These findings suggest that children's literature can be an effective medium for learning German while supporting character education. This study demonstrates that literary texts can offer meaningful language learning experiences, even in schools with limited resources.